2005
DOI: 10.1302/0301-620x.87b8.16161
|View full text |Cite
|
Sign up to set email alerts
|

Revision of cemented hip arthroplasty using a hydroxyapatite-ceramic-coated femoral component

Abstract: We report the clinical and radiological outcome of 86 revisions of cemented hip arthroplasties using JRI-Furlong hydroxyapatite-ceramic-coated acetabular and femoral components. The acetabular component was revised in 62 hips and the femoral component in all hips. The mean follow-up was 12.6 years and no patient was lost to follow-up. The mean age of the patients was 71.2 years. The mean Harris hip and Oxford scores were 82 (59 to 96) and 23.4 (14 to 40), respectively. The mean Charnley modification of the Mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 78 publications
3
24
1
Order By: Relevance
“…8 of 62 hips had mild-to-moderate thigh pain and no patients suffered from severe thigh pain. This compares favorably with other studies (Moreland and Moreno 2001, Raman et al 2005, Trikha et al 2005. Radiographically, several patients showed signs of load transfer distally, which suggests a possible reason for their mid-thigh pain.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…8 of 62 hips had mild-to-moderate thigh pain and no patients suffered from severe thigh pain. This compares favorably with other studies (Moreland and Moreno 2001, Raman et al 2005, Trikha et al 2005. Radiographically, several patients showed signs of load transfer distally, which suggests a possible reason for their mid-thigh pain.…”
Section: Discussionsupporting
confidence: 82%
“…Removal of such a stem would be more technically demanding and the outcome is likely to be worse thereafter. In an attempt to achieve sufficient initial stability with shorter stems, extensively porous-coated or HAcoated, canal-filling cobalt-chrome or titanium alloy stems have been used with good or excellent results (Lawrence et al 1994, Paprosky et al 1999, Moreland and Moreno 2001, Crawford et al 2004, Raman et al 2005, Trikha et al 2005, Reikerås and Gunderson 2006. At least initially, the biological fixation is probably most pronounced in the distal part of the stem because the contact between the stem surface and the host bone is more intimate in this region, and the surrounding bone stock is of better quality distally than in the compromised proximal bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12, 13 Long term clinical and radiological performance was excellent for fully HA coated femoral component. 13, 14 In spite of the good performance of HA coatings in revision surgery, overall performances of revision prosthesis have inferior results than primary. 15 One of the reasons of implant failure is bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…Uncemented hip revision after aseptic loosening has been promising in the short to medium time interval (Böhm and Bischel 2001, Moreland and Moreno 2001, Trikha et al 2005, Salemyr et al 2008) and several authors have reported good results in the long-term perspective as well (Wagner 1987, Paprosky et al 1999, Raman et al 2005, Reikerås and Gunderson 2006). Most stems used in these studies are extensively coated or distally anchored.…”
Section: Introductionmentioning
confidence: 99%